2021
DOI: 10.1021/acsanm.1c01504
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous-to-Crystal Transition in Quasi-Two-Dimensional MoS2: Implications for 2D Electronic Devices

Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDCs) have demonstrated a very strong application potential. In order to realize it, the synthesis of stoichiometric 2D TMDCs on a large scale is crucial. Here, we consider a typical TMDC representative, MoS 2 , and present an approach for the fabrication of well-ordered crystalline films via the crystallization of a thin amorphous layer by annealing at 800 °C, which was investigated in terms of long-range and short-range orders. Strong preferential cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“… 57 The doublet between the Mo 4+ and Mo 6+ doublets is assigned to Mo 5+ (MoO y S x ), an intermediate oxidation product. 58 , 59 For c-MoS 2 films, an additional low-intensity doublet at a lower BE compared to Mo 4+ was required to obtain a satisfactory fit. This doublet is denoted as Mo (4−δ)+ as it was attributed to more metallic Mo atoms present at the edges of MoS 2 crystals, 60 in the metastable 1T′ phase of MoS 2 , 61 or MoS 2– x subsulfide.…”
Section: Resultsmentioning
confidence: 99%
“… 57 The doublet between the Mo 4+ and Mo 6+ doublets is assigned to Mo 5+ (MoO y S x ), an intermediate oxidation product. 58 , 59 For c-MoS 2 films, an additional low-intensity doublet at a lower BE compared to Mo 4+ was required to obtain a satisfactory fit. This doublet is denoted as Mo (4−δ)+ as it was attributed to more metallic Mo atoms present at the edges of MoS 2 crystals, 60 in the metastable 1T′ phase of MoS 2 , 61 or MoS 2– x subsulfide.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, after the full charging, the aforesaid peaks almost recover to the original state of TS-MoSe 2 , while the Mo foil-related features disappear, indicating that the discharging and charging processes of TS-MoSe 2 during the initial cycle are nearly fully reversible. It should be noted that the Mo K-edge XANES spectra of formed metallic Mo and the regenerated MoSe 2 are slightly different from those of corresponding Mo foil and pristine TS-MoSe 2 , which may be caused by the ligand effect of imidazole and amorphous nature, respectively 41 , 42 . A similar change trend is also observed in the Se K-edge XANES (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, the Mo K edge XANES spectra for both versions of crystallized MoS 2 are very similar, corroborating that the final products of both amorphous phases have the same structure after crystallization. 28,33 However, a detailed comparison indicated that, for crystallized MoS 2 originating from amorphous MoS 2 , the intensity of the so-called white-line is lower and the overall shape of the XANES spectrum is more rounded compared to the counterpart XANES spectrum of MoS 2 originating from MoS 4 , suggesting that the former structure is less ordered. The results of the real-space fitting of the EXAFS data of the amorphous and crystalline phases are summarized in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These values are in line with previously reported results. 28,33,36,37 The coordination numbers of the first (Mo−S) and second (Mo− Mo) coordination shells are 5.90 and 4.19 for crystallized MoS 2 originating from MoS 2 and 6.29 and 7.67 for that originating from MoS 4 , leading to the conclusion that the crystalline MoS 2 phase originating from MoS 4 is clearly better ordered. We would like to emphasize that the conclusion from the EXAFS experiment is in excellent agreement with the XRD analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%